History of religions which came to Central Asia - Zuuridinov, Oskonbay (Scientific Journal of Faculty of Theology, 2020)
In this paper we mentioned briefly about religions and their history which came to Central Asia. Also we laid stress on terms above-mentioned of religions and explained the meaning of them.